Study of Interest of Farmer Group Like Forward in The Use of Trichoderma Asperellum in Rice Cultivation in Bomba Village, Sigi District - Sayani sayani; Sri Sudewi; Kasman Jaya; Renaldi renaldi; Abdul Rahim Saleh; Ratnawati ratnawati (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
The intensive and excessive use of chemical fertilizers and pesticides can have various impacts on soil fertility, farmers' health, and impacts on the environment. One alternative to minimize this impact is by using microorganisms, namely the fungus Trichoderma asperellum. This study aims to find out how interested or interested members of the Suka Maju Farmer Group in Bomba Village, Sigi Regency, Central Sulawesi, are in applying Trichoderma asperellum to rice cultivation land. The method used is quantitative descriptive analysis with primary data collection including observation, direct interviews, and semi-structured questionnaires that have been prepared, while secondary data is obtained from literature studies or source tracing related to research issues. Respondents in this study were all members of the Suka Maju Farmer Group, totaling 25 people. Data analysis used descriptive analysis using Microsoft Excel 2013 software. The observational variables of this study were the internal and external factors of the respondents, the level of interest of the respondents based on indicators of disinterest, lack of interest, interest, and very interest as well as the distribution of interest indicators (satisfaction, willingness, spirit, skill) with the use of T. asperellum. The results obtained were that members of the Suka Maju Farmer Group in Bomba Village had an interest of ≥ 70% in the use of T. asperellum in rice cultivation. To attract farmers' interest, counseling strategies, training, and continuous assistance from agricultural extension workers are needed, information delivery using effective and optimal media and supported by effective communication between extension farmers and related parties.